The Development of Basic Practical Skills in Volleyball Based on Davies’ Instruction Model of Matthayomsuksa 3 Students - Sopalerd, Nutchanat; Hattaprom, Prayong; Janghan, Surakan; Deerasamee, Sirimanee (Journal for Developing the Social and Community, 2023)
The purposes of this research were to: 1) develop basic practical skills in volleyball learning activities with Davies concept learning activities of Matthayomsuksa 3 students to be effective in accordance with 80/80, 2) compare basic practical skills in volleyball of Matthayomsuksa 3 students who studied using Davies' conceptual learning activities after school with the criteria of 80, and 3) study on satisfaction with learning activities using basic practical skills in volleyball based on Davies’ Instruction Model. The samples of this research were 42 students in Matthayomsuksa 3/4 of Muang Kalasin School, Mueang District, Kalasin Province who enrolled in the second semester of 2022 academic year. These students were randomly selected by cluster random sampling method. The instruments used in this research were lesson plans, basic practical skills in volleyball test and student satisfaction questionnaire. Statistics used in data analysis were percentage, mean and standard deviation. The research found that: 1) the activities of learning basic practical skills in volleyball based on Davies concept had an efficiency of 81.07/83.62, 2) the basic practical skills in volleyball based on Davies concept after school, with a total score of 83.62 was very good and above the criteria, and 3) students were satisfied with basic practical skills in volleyball learning activities based on Davies' concept of Matthayomsuksa 3 students overall (= 2.13, S.D.= 0.91).